The organization of public-private cooperation for productive development policies - Jorge Cornick (Inter-American Development Bank (IDB), 2013)
Productive development policies (PDPs)-what used to be called industrial policies-are increasingly recognized as an essential part of the development toolkit, and the need for public-private cooperation is increasingly viewed as a key element for the successful design and implementation of such policies. If so, how should the cooperation be organized and how should the public sector organize itself to successfully participate in it? This paper suggests that public sector organization should be a response to three key variables: the scope of the PDP, the scope of the intended cooperation, and the organizational characteristics of the private sector. It further proposes the appropriate selection of public sector participants; the alignment of policy, political, and organizational time frames; the ensured quality of the bureaucracy; the protection against private and bureaucratic capture and against unbounded financial risk; and a reasonable regulatory environment of key elements for success.
hdl:11319/4590
Keywords: O140; O250; L520; L530; 330; Industrial policy; sector planning; entrepreneurship; innovation; entrepreneurship; technological change